Sosialisasi Pemahaman Laporan Keuangan Dalam Menunjang Usaha Mikro Kecil dan Menengah (UMKM) Melalui Metode Aplikasi Di Kelurahan Alak Kecamatan Alak Kota Kupang - Hermyn Hina; Dedy Raidons Se’u (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2022)
The Covid-19 pandemic period that has occurred since February 2020 which has hit the Indonesian nation until now and natural disasters caused by tropical cyclone Seroja that hit East Nusa Tenggara Province including Kupang City from April 3 to 5, 2021, has a bad impact on financial management in an institution or organization that is profit-oriented or non-profit oriented, this is due to the large number of unexpected expenses that affect the financial statements in a company or organization. The results achieved in the PKL Community Service activity "Socialization of Understanding financial statements in supporting MSMEs through the Application Method in Alak Village" are as follows: The partner in this case MSMEs in Alak District become more understanding of the importance of regular financial statements through the application method so that financial statement management is easier to access and helps MSMEs develop properly; and the creation of an electronic-based financial report application so that it can be used and utilized by MSMEs in knowing the prospects for income and cost expenditure in improving MSMEs in Alak District; as well as the creation of a sustainable financial reporting process so that MSMEs can grow and develop in accordance with the goals of MSMEs in Alak District.